Pengembangan LKPD Materi Sejarah Kerajaan Singosari Untuk Pembelajaran IPS Kelas Pendidikan dan Pengembangan Seni Tradisi - Elvira Zulfah Aliyah; Agung Wiradimadja (Journal Pendidikan Ilmu Pengetahuan Sosial, 2023)
Traditional arts have the potential to be internalized in social studies learning. Unfortunately, social studies teachers at SMPN 24 Malang have not developed teaching materials that include elements of traditional arts even though there is already a PPST class (art class program for junior hight school). Teachers also have not improved teaching materials that apply a contextual approach in the form of the local history of the Malang area. This research and development aim to 1) produce LKPD products for the history of the Singosari Kingdom for PPST class for social studies subject by integrating the temple of Batik patterns, and 2) Do test the feasibility of the developed LKPD products. Product development in this study uses an Research and Development (R&D) approach with ADDIE design. Data collection was carried out using instruments in the form of validation sheets and student respon questionnaires. Before distributing the questionnaire to the product trial subjects, the validity and reliability of the questionnaire were tested. The LKPD feasibility test through validation is carried out by material experts, learning media experts, and language experts. The implementations of LKPD was carried out in a limited group of 29 students. Based on the results of the validation and trial tests, this LKPD is categorized as "Very Eligible" to be applied in PPST class social studies learning. LKPD improvements were also made based on input from validators and test subjects